Regulation of drugs in Andhra pradesh: An overview - BALAMURALIDHAR V; KEMPAIAH SURESH (International Journal of Pharma and Bio Sciences, 2017)
Andhra Pradesh has been one of the pioneer States in India with an exemplary track record. The State of Andhra Pradesh has some of the country’s most dynamic entrepreneurs who are original and fast-paced in their thinking and focused in their drive for growth and profitability. Drugs Control Administration regulates the manufacture, sale and distribution of drugs to ensure their quality and efficacy. Accounting for 16 percent of the country’s total industrial output and 18percent of the country’s total investment, Andhra Pradesh is one of the most industrialised states in the country. It has a strong base of educational institutions imparting courses in Pharmacy and some of the institutions have international repute to its credit. Andhra Pradesh is one of the fastest growing states in the Country and nearly 500 pharma and biotech companies are housed in the State. Andhra Pradesh is a vibrant pharmaceutical manufacturing hub for Bulk Drugs. The State has knowledge based institutions and skilled human resource in the state.. In this the author has made some observations in field of pharmacy and the Regulation of Drugs in Andhra Pradesh.